(De)lithiation of spinel ferrites Fe3O4, MgFe2O4, and ZnFe2O4: a combined spectroscopic, diffraction and theory study. Issue 45 (17th November 2020) - Bock, David C.; Tallman, Killian R.; Guo, Haoyue; Quilty, Calvin; Yan, Shan; Smith, Paul F.; Zhang, Bingjie; Lutz, Diana M.; McCarthy, Alison H.; Huie, Matthew M.; Burnett, Veronica; Bruck, Andrea M.; et al.
Abstract : Combined X-ray absorption spectroscopy, synchrotron X-ray diffraction, and density functional theory elucidate (de)lithiation mechanisms for the spinel ferrites MFe2 O4 (M = Fe 2+, Mg 2+, Zn 2+ ). Abstract : Iron based materials hold promise as next generation battery electrode materials for Li ion batteries due to their earth abundance, low cost, and low environmental impact. The iron oxide, magnetite Fe3 O4, adopts the spinel (AB2 O4 ) structure. Other 2+ cation transition metal centers can also occupy both tetrahedral and/or octahedral sites in the spinel structure including MgFe2 O4, a partially inverse spinel, and ZnFe2 O4, a normal spinel. Though structurally similar to Fe3 O4 in the pristine state, previous studies suggest significant differences in structural evolution depending on the 2+ cation in the structure. This investigation involves X-ray absorption spectroscopy and X-ray diffraction affirmed by density functional theory (DFT) to elucidate the role of the 2+ cation on the structural evolution and phase transformations during (de)lithiation of the spinel ferrites Fe3 O4, MgFe2 O4, and ZnFe2 O4 . The cation in the inverse, normal and partially inverse spinel structures located in the tetrahedral (8a) site migrates to the previously unoccupied octahedral 16c site by 2 electron equivalents of lithiation, resulting in a disordered [A]16c [B2 ]16d O4 structure. DFT calculations support the experimental results, predicting full displacement of the 8a cation to the 16c site at 2 electron equivalents. Substitution of the 2+ cation results in segregation of oxidized phases in the charged state. This report provides significant structural insight into the (de)lithiation mechanisms for an intriguing class of iron oxide materials.